MÉTODO DE OTIMIZAÇÃO TOPOLÓGICA APLICADO A ESCOAMENTOS INCOMPRESSÍVEIS LAMINARES TRANSIENTES BIDIMENSIONAIS - Matos, Victor Elias Rosa Moscon de (2021)
Since before the beginning of industrial activity in the world, flow machines have played an important role in the development of humanity. The importance of the study and knowledge of fluid flow phenomena is essential for the development of new technolog